Victim Oriented Model for Resolving Traffic Accident Cases in Pursuit of Reforming Indonesia’s Criminal Law Policy - Rini Widiyanti; Anthon F. Susanto; Rd. Hj. Dewi Asri Yustia (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Traffic accidents in Indonesia continue to cause significant human, social, and economic losses; however, their legal resolution remains predominantly retributive and insufficiently responsive to victims’ rights and recovery. This study aims to analyze the legal formulation for determining victims in traffic accident cases from a victimological perspective and to develop a victim-oriented settlement model as part of Indonesia’s criminal law policy reform. This research employs a normative juridical method with a descriptive-analytical orientation using statute, conceptual, comparative, and supportive empirical approaches. The comparative analysis examines restorative and victim-oriented mechanisms in Japan, the Netherlands, and Singapore, while empirical input was obtained through semi-structured interviews with police officers, prosecutors, legal experts, and traffic accident victims as supportive qualitative material. The findings reveal three principal weaknesses in the current system: the marginalization of victims within criminal proceedings, the absence of standardized criteria for determining victim status, and the weak implementation of compensation or restitution mechanisms. The study further found that restorative and victim-oriented approaches can be integrated into formal criminal justice without eliminating offender accountability. In response, this article proposes a victim-oriented model consisting of four core elements: victim determination based on victimology, structured mediation facilitated by law enforcement, accessible and enforceable restitution mechanisms, and active victim participation throughout the settlement process. This study is limited by its primarily doctrinal character and supportive empirical scope. The originality of this study lies in integrating victimology-based victim determination with a structured restorative justice framework specifically designed for traffic accident cases in Indonesia.